Neonatal tetanus with intestinal atresia, the importance of multidisciplinary management: a case report - Taimur Iftikhar Qureshi; Muhammad Arshad (Journal of the Pakistan Medical Association, 2025)
Neonatal infection begins through the umbilical cord when the stump is handled with an unsterile instrument. Most cases of neonatal tetanus develop symptoms during the first eight days of life. It is rarely reported with intestinal atresia. We report the case of an eight-day-old baby boy belonging to a Pashtun family, weighing 1.9 kg, admitted with complaints of decreased activity and intolerance to feed, with resultant non-bilious vomiting. Clinical examination revealed a distended soft abdomen, generalised rigidity with opisthotonus, and lockjaw. With the clinical diagnosis of tetanus, management was started using tetanus immunoglobulin and intravenous antibiotics. X-ray of the abdomen was suggestive of jejunal atresia. Surgery was done after one week of medical management for tetanus, and on surgical exploration, proximal jejunal atresia was confirmed. Resection anastomosis was done. The post-operative period was uneventful, and the neonate was discharged on oral feed. In such cases, immediate surgical intervention is not required, and multidisciplinary team management is recommended.